1999
DOI: 10.1165/ajrcmb.20.2.3062
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of the Tracheal Epithelium

Abstract: We have developed a unique in vitro reconstitution system for tracheal epithelia of guinea pigs. In the system, a human amnion membrane was used as a basement membrane and the tracheal epithelial cells were cultured on the epithelial side of the membrane. Three weeks later, the tracheal fibroblasts were co-cultured on the serosal side of the amnion membrane and the culturing was continued for an additional 10 d. The morphology of the cultured epithelial cells consisted of a pseudostratified columnar ciliated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
3
50
0
3
Order By: Relevance
“…Respiratory epithelial cells and fibroblasts were cultured using the coculture system described in our previous studies [Ziegelaar et al, 2002;Nur Adelina et al, 2007]. Stimulatory effects of fibroblasts facilitated epithelial cell differentiation into mainly basal, ciliated and goblet cells with increased mucin secretion [Goto et al, 1999;Kobayashi et al, 2006Kobayashi et al, , 2007. Respiratory epithelium cells obtained using a coculture system produce significantly more basal cells and stem cell gene expression, suggesting a high potential to regenerate a normal tracheal epithelium in vivo [Hong et al, 2004;Nur Adelina et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory epithelial cells and fibroblasts were cultured using the coculture system described in our previous studies [Ziegelaar et al, 2002;Nur Adelina et al, 2007]. Stimulatory effects of fibroblasts facilitated epithelial cell differentiation into mainly basal, ciliated and goblet cells with increased mucin secretion [Goto et al, 1999;Kobayashi et al, 2006Kobayashi et al, , 2007. Respiratory epithelium cells obtained using a coculture system produce significantly more basal cells and stem cell gene expression, suggesting a high potential to regenerate a normal tracheal epithelium in vivo [Hong et al, 2004;Nur Adelina et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…The basement membrane was reported to influence differentiation, migration and proliferation of epithelial cells and is im- portant in maintaining structural tissue integrity [Kobayashi et al, 2006[Kobayashi et al, , 2007Nomoto et al, 2008]. Another previous study suggested that epithelial-fibroblast interaction plays a crucial role in the organogenesis, morphogenesis and differentiation of the tracheal epithelial cells [Goto et al, 1999]. Although the implantation of the cell and fibrin construct demonstrated the regeneration of pseudostratified columnar epithelium lining, the cells found within this epithelium 4 weeks after surgery actually comprised cells in heterogenous morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…3). Recognising the effects of mesenchymal cells on epithelial proliferation and differentiation from earlier work (197) (198). The presence of hMSCs altered the temporal pattern of mucin secretion by the epithelial monolayer, but the authors noted a prominent limitation in their model that when the MSCs were induced towards a chondrogenic lineage, they detached from the insert before any discernible effects on the bronchial epithelium could be observed, negating the coculture system.…”
Section: In Vitro Respiratory Drug Development and Disease Modelsmentioning
confidence: 99%
“…However, this biomimetic seeding strategy has had some success in humans, when seeding chondrocytes differentiated from MSCs on the exterior surface and epithelial cells on the interior surface [146]. Other combinations of cells utilized for trachea repair are epithelial cells and fibroblasts [172], endothelial cells and epithelial cells [173], chondrocytes and fibroblasts [136], fibroblasts and muscle cells [148], and bone marrow stromal cell-derived chondrocytes and epithelial cells [152,146]. Walles et al evaluated an even greater number of cell types; seeding chondrocytes, bone marrow-derived smooth muscle cells, bone marrowderived endothelial cells, or respiratory epithelium on a decellularized matrix [150].…”
Section: Multiple Cell Typesmentioning
confidence: 99%